2021
DOI: 10.3390/su13137035
|View full text |Cite
|
Sign up to set email alerts
|

University Social Responsibility during the COVID-19 Pandemic: Universities’ Case in the BRICS Countries

Abstract: University social responsibility (USR) is an important assessment criterion of the QS Stars. In the context of the COVID-19 pandemic, the social orientation of universities as intellectual leaders in the development of society gains particular importance. The research purpose is to analyze the impact of the COVID-19 pandemic on the university activity directions in the framework of strategies (USR). An empirical assessment of the level and complementary factors of USR in the BRICS countries (Brazil, Russia, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 51 publications
0
27
0
1
Order By: Relevance
“…"Critical analysis does not only criticize, but it also references ideas and practices that are essential, needed, or critical for something to happen" (Hill Collins et al 2021, p. 691). As intellectual front-runners and visionaries, university leaders are increasingly called on to incorporate social responsibility in their organizational strategies (Rababah et al 2021). They are drivers and masters of social change in concrete terms.…”
Section: University Social Responsibilitymentioning
confidence: 99%
“…"Critical analysis does not only criticize, but it also references ideas and practices that are essential, needed, or critical for something to happen" (Hill Collins et al 2021, p. 691). As intellectual front-runners and visionaries, university leaders are increasingly called on to incorporate social responsibility in their organizational strategies (Rababah et al 2021). They are drivers and masters of social change in concrete terms.…”
Section: University Social Responsibilitymentioning
confidence: 99%
“…According to Ali et al (2020), "Universities across the globe need to undertake social responsibility as an integral process of the organization and mold their activities of teaching education and training accordingly"; in this sense, their research indicates the practical approaches that can be undertaken by universities to legitimize their social responsibility initiatives, also shedding light on the fact that the social responsibility of universities differs "in nature from corporate social responsibility since the nature of institutional operations and objectives are inherently different from business organizations". Rababah et al (2021) showed that "University management creativity, effective communication with the public and stakeholders, the quality of the educational process and the development of scientific activities stimulate USR development", with special regard to the BRICS countries and, as such, these should be used as the basis for the strategic planning of activities in the context of the continuing COVID-19 pandemic.…”
Section: Recent Contributions In the Academic Fieldmentioning
confidence: 99%
“…On the communal level, this load decreases productivity, especially food production, and maintains the vicious circle of increased hunger, infection, disease, poverty, and socioeconomic and political instability (Silverio et al, 2021). Hyper infectious nature of SARS-CoV-2, especially it is few variants, countries including BRICS territories have taken unrivaled initiatives to combat COVID-19 transmission, ranging from the limited social exposure, revocation of public transit to social isolation (Zhao et al, 2020;Dash et al, 2021;Popkova et al, 2021;Rababah et al, 2021). Distinct nutrient deficiency or protein-energy deprivation has been shown to detrimentally affect the infection combating prospects along with diminished immunity level (Ambrus and Ambrus, 2004;Silverio et al, 2021).…”
Section: Equation Of Covid-19 and Malnutritionmentioning
confidence: 99%
“…Many of these bioactive phytochemicals alleviate psychosomatic stress (Fedotova et al, 2017;Aubry et al, 2019;Soni et al, 2020b). COVID-19 pandemic effects have distress consequences (Clemente-Suárez et al, 2020;Popkova et al, 2021;Rababah et al, 2021); and herbal medicinal preparation or bioactive phytochemical-rich diet can moderate these social distress disorders (Aubry et al, 2019). Due to uncertainty on COVID-19 pandemic, anxiety and similar disorders become frequent.…”
Section: Herbal Remediesmentioning
confidence: 99%
See 1 more Smart Citation